Performance Analysis of Inverse Kinematics-Based Balance Control for Hexapod Stair Navigation - SYAFFEL SEAN RIZKINATA HERYAMAN; KHAIRUL ANAM; WAHYU MULDAYANI; ALI RIZAL CHAIDIR; DEDY WAHYU HERDIYANTO; CANDRA PUTRI RIZKIYAH RAMADHANI; AVIQ NURDIANSYAH PUTRA; MUCHAMAD ARIF HANA SASONO (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Maintaining body stability is a key challenge for hexapod robots in stair navigation. This study proposes an inverse kinematics (IK)-based approach for dynamic balance control using real-time joint angle computation. Experimental results show that the method maintains body orientation near a neutral position, achieving a minimum pitch angle of 7.3°, thereby improving stability and reducing mechanical collision risk. System performance is also influenced by actuator speed and battery voltage.